Asertivitas Korban Bullying dan Penanganannya (Studi Kasus pada Siswa di SMA Negeri 2 Soppeng) - Oktaviani, Putri; Umar, Nur Fadhilah; Pandang, Abdullah (Universitas Negeri Makassar, 2024)
This research discusses the assertiveness of victims of bullying that occurs among students at SMA Negeri 2 Soppeng. The main studies of this research are: (1) Description of the assertiveness of bullying victims (ARH) at SMA Negeri 2 Soppeng. (2) Factors that influence the assertiveness of bullying victims (ARH) at SMA Negeri 2 Soppeng. (3) Handling efforts to overcome the problem of assertiveness of bullying victims (ARH) at SMA Negeri 2 Soppeng. This research uses a qualitative approach with a clinical case study type of research. Data collection through interviews and observations. Data analysis used descriptive analysis with the Milles and Huberman model. The research results obtained were (1) Description of assertiveness in ARH subjects, namely not being able to express or express feelings honestly, feeling afraid and embarrassed or anxious when they want to complain or report their problems to other people or those closest to them. and not putting up a fight when he is being bullied. (2) factors that influence low assertiveness in victims of ARH bullying, namely psychological condition factors such as low self-confidence, worry about other people's judgments as well as anxiety and fear of being the target of further bullying as well as parenting style factors from authoritarian parents. (3) Based on the causes of the problems experienced by ARH, the intervention that is considered the most effective compared to other interventions in increasing the assertiveness of ARH bullying victims is by providing assertive training from a behavioral counseling approach